AN INSIGHT INTO EBONY AND EBONIZATION OF WOOD (Applied Biological Research, 2024)
Ebony, a dense black/brown hardwood coming from several species of   genus Diospyros, is facing a scarcity in market due to trade ban. This constraint   in material availability has led to the adoption of ebonization techniques in other   wood, wherein wood is treated to mimic the distinctive dark black colour of   ebony. Ebonization process has become an important factor in industries looking   for imitated wood products to meet the consumer preferences for aesthetic   appeal of ebony-like wood. In this paper a concise insight into the current status   of ebony (Diospyros ebenum) in India has been given with emphasis on the   ebonization. The paper reviews the effectiveness of various ebonization methods,   with focus acetate, as the most promising approach and challenges in this process.
Keywords: Black colour; coating; ebonization; Diospyros ebenum